The videomaker guide to video production - York, Matt, ....-; Burkhart, John, ....- (Amsterdam : Elsevier, 2008)
From the editors of Videomaker Magazine comes this new edition that you have been waiting for. The Videomaker Guide Digital Video, fourth edition, provides information on all of the latest cutting edge tools and techniques necessary to help you shoot and edit video like the pro's. Learn about equipment, lighting, editing, audio, high definition, and all aspects of video from the leading experts on videography! * Now packed with high definition articles! * Learn how to use your skills for vidcasting (video podcasts) * Advice from the experts with quick solutions for video production
Keywords: Video